Analysis of Strategies to Prevent Cyberbullying and Harassment in Online Media Platforms - Mukramin, Sam’un; Ismail, Lukman; Fatmawati , Fatmawati; Nursida, Andi (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2024)
Cyberbullying and harassment in online media platforms pose significant challenges, necessitating effective prevention strategies. This research comprehensively analyzes various prevention strategies, including technological, educational, community-based, policy, and collaborative interventions. Findings underscore the importance of a multifaceted approach, combining technological solutions with educational initiatives, community engagement, policy frameworks, and multi-stakeholder collaboration. While successful interventions empower individuals with digital literacy, empathy, and peer support, challenges such as sample biases, self-reporting biases, and ethical considerations must be addressed. By synthesizing insights from existing literature and theoretical frameworks, this research informs theory, practice, and policy in combating cyberbullying and harassment, paving the way for a safer and more respectful digital environment.